Galaxy flows in cosmic filaments - Korhonen, Suvi (My University, 2021)
In the universe galaxies are assembled into the cosmic web, consisting of voids, walls, galaxy clusters and filaments. Filaments are elongated matter flows connecting the clusters together. Because of the non-uniform matter distribution in the universe, galaxies acquire peculiar velocities deviating from the expansion velocity of the universe. These peculiar motions trace the formation history of the cosmic web. This thesis studies the effect of the filament environment on the peculiar motions of central galaxies using the hydrodynamical EAGLE simulation and filaments identified with the Bisous method. The magnitude of the galaxy peculiar velocity and the alignment angle between the peculiar velocity vector and the filament spine are measured. The peculiar motions inside and outside of filaments are compared and measured with fixed geometric properties of filaments and baryonic properties of galaxies. The analysis is done with fixed group mass to avoid the effect of the local environment on the peculiar motions. The analysis reveals that the central galaxies move more slowly and more parallel to the filament spines inside of filaments than on the outside. The peculiar velocities increase and motions become more parallel in the shortest and longest filaments. In the direction parallel with the filament spines, the alignment of motions of central galaxies in low mass groups indicate that filaments transport galaxies into clusters. Perpendicular to the filament spines, the peculiar velocities of central galaxies in low mass groups are the highest near the filament edges and decrease on both sides. Massive groups are found to concentrate in short filaments and near the filament spines. The central galaxies in the massive groups have the most parallel motions, both inside and outside of filaments. In general, the peculiar motions depend on the group mass, velocities decreasing with increasing group mass. The baryonic properties of galaxies are found to have no effect on the peculiar motions. Together the results hint that in the parallel direction the peculiar motions are the most affected by the clusters connected to the filaments, while the galaxy number densities within filaments determine the motions in the perpendicular direction. This thesis broadens the view on how the filament environment affects the flows of galaxies.
Keywords: peculiar motions, filaments, large-scale structure, simulations